Методика лабораторных исследований уровенного режима водохранилищ, расположенных в каскадах - Pastukhov, Сергей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
Laboratory research procedure for water level variation of tandem reservoir system is presented. It particularly includes different hydrodynamic disaster initiation scenarios. Based on reservoir stock of the Republic of Belarus two variants of reasonable tandem reservoir system arrangement are noted: with or without channel segment between reservoirs. There is particular part of the article dedicated to modeling scale validation, as well as to geometric and dynamic similarity criteria. Laboratory installation diagram and developed on the Vitebsk region objects data waterworks models appearance are submitted. The proposition of presented procedure possible usage for water level variation assessment at tandem reservoir systems in case of emergencies is made.